Language Issues in former Yugoslav Space: A Commentary - Friedman, Victor A. (Aegean Working Papers in Ethnographic Linguistics, 2020)
Although the break-up of Yugoslavia has spawned an enormous literature in many fields, Language Issues in former Yugoslav Space: Current Perspectives (Aegean Working Papers in Ethnographic Linguistics Vol. 2, No. 1), 2018 ed. by Roswitha Kersten-Pejanić (general ed. Costas Canakis), is a welcome assessment of some aspects of the current state of affairs from an ethnolinguistic standpoint. The varied articles in this volume each deserve individual attention, and thus my remarks address the articles separately. [...]